2006
DOI: 10.1165/rcmb.2005-0326oc
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic Receptor and Cyclic Stretch-Mediated Inflammatory Gene Expression in Intact ASM

Abstract: We tested the hypothesis that cholinergic stimulation and cyclic stretch regulate inflammatory gene expression in intact airway smooth muscle by measuring mRNA expression in bovine tracheal smooth muscle using limited microarray analysis and RT-PCR. Carbachol (1 microM) induced significant increases in the expression of cyclooxygenase (COX)-1, COX-2, IL-8, and plasminogen activator, urokinase type (PLAU) to levels ranging from 1.3- to 3.1-fold of control. Sinusoidal length oscillation at an amplitude of 10% mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
53
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 49 publications
(40 reference statements)
4
53
1
Order By: Relevance
“…These results extend previous observations by others who have shown that muscarinic receptor stimulation can induce IL-8 production by bronchial epithelial cells, and leukotriene B 4 production by monocytes, macrophages and bronchial epithelial cells [6,[8][9][10]27]. Muscarinic receptor stimulation using carbachol was also previously shown to regulate pro-inflammatory gene transcription of IL-6 and -8 and COX-2 induced by mechanical stimulation of airway smooth muscle strips [19]. Our current findings confirm these studies and provide novel insights as we demonstrate a strong synergistic interaction with the response induced by cigarette smoke extract.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These results extend previous observations by others who have shown that muscarinic receptor stimulation can induce IL-8 production by bronchial epithelial cells, and leukotriene B 4 production by monocytes, macrophages and bronchial epithelial cells [6,[8][9][10]27]. Muscarinic receptor stimulation using carbachol was also previously shown to regulate pro-inflammatory gene transcription of IL-6 and -8 and COX-2 induced by mechanical stimulation of airway smooth muscle strips [19]. Our current findings confirm these studies and provide novel insights as we demonstrate a strong synergistic interaction with the response induced by cigarette smoke extract.…”
Section: Discussionsupporting
confidence: 91%
“…The regulatory role of acetylcholine in these synthetic airway smooth muscle cell responses is largely unknown. A study using bovine tracheal smooth muscle strips showed that stimulation with carbachol resulted in increased expression of IL-8, cyclooxygenase (COX)-1 and -2 at the mRNA level [19]. This study [19], together with the fact that airway smooth muscle expresses muscarinic M2 and M3 receptors in abundance, suggests a role for these receptors in release of mediators.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, tiotropium bromide prevented airway eosinophilia in allergen-challenged animals. It is possible that acetylcholine promotes the release of chemokines and cytokines from airway structural cells, as reported for airway epithelial cells and airway smooth muscle [14][15][16], in order to attract inflammatory cells to the airways, and functionally interacts with the growth factors or cytokines that are released by these cells to induce direct remodelling effects on structural target cells, similar to what has been observed for airway smooth muscle remodelling [2,11]. Although transactivation of the epidermal growth factor receptor by muscarinic receptors has been reported in conjunctival goblet cells [33], no detailed molecular studies investigating the role of muscarinic receptors in the proliferation and hypertrophy of airway mucous glands exist.…”
Section: Discussionmentioning
confidence: 88%
“…In vitro studies have revealed that prolonged stimulation of muscarinic receptors enhances airway smooth muscle contractile protein expression, pro-mitogenic signalling and cell proliferation [1,11,12]. Moreover, muscarinic receptor stimulation induces cell proliferation of primary cultured pulmonary fibroblasts [13], and triggers the release of proinflammatory mediators, including leukotriene B 4 , from airway smooth muscle and airway epithelial and inflammatory cells [14][15][16][17]. These pro-inflammatory actions of acetylcholine may be enhanced in inflammatory airways diseases, since M 3 expression and function are increased on neutrophils from COPD patients [18].…”
mentioning
confidence: 99%